A reusable electret filter media based on water droplet charging/cleaning. (16th January 2023) - Wang, Jiu-Si; Cai, Rong-Rong; Wu, Shun-Jie; Zhang, Li-Zhi
Graphical abstract: Highlights: A PTFE electret membrane with excellent regeneration performance is developed. Water droplet rolling simultaneously achieves membrane cleaning and recharging. Hydrophilic PM2.5 is easier to clean by droplets rolling than hydrophobic PM2.5 . Charge transfer rate of droplet-hydrophobic membrane increases linearly with their contact area. Abstract: Electret filter media has been considered as the most effective and economical filtration material due to its additional electrostatic filtration effect. However, the regeneration and recycling of electret filter media is a great challenge, as its stored charge would dissipate during filtration process, resulting in a significant efficiency reduction after cleaning. To address this problem, based on liquid–solid contact electrification (C-E) theory and self-cleaning property of hydrophobic surface, we successfully designed and fabricated a reusable PTFE electret filter membrane. After water droplets charging/cleaning, the surface charge of the membrane can be recovered to 100–110%, and the pressure drop can be restored to > 93%, exhibiting an excellent regeneration performance. Then the effect of particle wettability on cleaning performance was investigated. The hydrophilic PM2.5 on hydrophobic surface was found to be easier to clean by droplets rolling than the hydrophobic PM2.5 due to its stronger adhesion to the droplets. Furthermore, based on the theory of ion transfer at the solid–liquid interface, the charge evolution of the hydrophobic PTFE surface during the triboelectric electrification of water droplets was modeled. The rate of ion transfer between water droplets and hydrophobic surfaces depends linearly on the actual liquid–solid contact area. The charge saturation value of a solid surface is related to its ionic binding sites and the dielectric properties. The study promotes the development of reusable electret filters, and advances the understanding of the triboelectric properties of droplets on hydrophobic surfaces.